1994
DOI: 10.1016/0735-1097(94)90599-1
|View full text |Cite
|
Sign up to set email alerts
|

Dipyridamole-dobutamine echocardiography: A novel test for the detection of milder forms of coronary artery disease

Abstract: Routine dobutamine addition to dipyridamole stress testing is clinically useful and well tolerated. It expands the spectrum of the disease detectable by pharmacologic stress echocardiography and allows documentation of milder forms of coronary artery disease that can be missed by conventional dipyridamole or dobutamine stress echocardiography.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(15 citation statements)
references
References 22 publications
1
14
0
Order By: Relevance
“…However, markedly differing responses have been described in the literature for cases with angiographically detected flow reduction. Some studies, using visual assessment of the ultrasound images, have reported either no response or a worsening in thickening in an ischemic segment during a DIP/adenosine challenge and have related the lack of response to the degree of epicardial vessel stenosis [6,7,10]. In contrast others studies, investigating patients with similar epicardial vessel stenosis have shown either an apparent increase in function during the infusion of DIP/adenosine or no response (based on changes in wall motion score index WMSI) [8,9,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, markedly differing responses have been described in the literature for cases with angiographically detected flow reduction. Some studies, using visual assessment of the ultrasound images, have reported either no response or a worsening in thickening in an ischemic segment during a DIP/adenosine challenge and have related the lack of response to the degree of epicardial vessel stenosis [6,7,10]. In contrast others studies, investigating patients with similar epicardial vessel stenosis have shown either an apparent increase in function during the infusion of DIP/adenosine or no response (based on changes in wall motion score index WMSI) [8,9,[11][12][13][14].…”
Section: Discussionmentioning
confidence: 99%
“…In the setting of single vessel disease, ambiguous findings have been reported during vasodilators SE in patients with epicardial CAD [6,7,[9][10][11][12][13][14]. Some have reported an improvement while others have shown worsening in contractility in segments as measured by the global wall motion score index (WMSI).…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…For both tests, this infusion protocol cannot be considered truly state of the art because recently it was shown that atropine (up to 1 mg over 4 minutes) further rises the test sensitivity without decreasing specificity for both dobutamine27 and dipyridamole.28 Also, it has been shown that the immediate addition of dobutamine to dipyridamole negative tests increases the sensitivity of dipyridamole echocardiography without affecting specificity. 40 Furthermore, all of our patients could perform adequate exercise, a majority were men, many had had a previous myocardial infarction and consequently presumed coronary artery disease, and most of them were receiving antianginal medication at the time of stress testing. Therefore, this group of patients may not be quite representative for those patients who will undergo physical or pharmacological stress echocardiography testing.…”
Section: Study Limitationsmentioning
confidence: 99%
“…Dual-agent protocols could overcome these limitations utilizing the combination of reduced myocardial blood supply and increased oxygen demand to provoke myocardial ischemia. The dipyridamole-atropine (Dip-Atro) protocol was published in 1993 [8] and dipyridamole-dobutamine (Dip-Dob) protocol in 1994 [9,10].…”
Section: Introductionmentioning
confidence: 99%